PENGGUNAAN WORKING WITH WORDS SEBAGAI STRATEGI UNTUK MENINGKATKAN KOSAKATA BAHASA INGGRIS - Jolanda Pilongo (Jurnal Imagine, 2021)
Vocabulary learning plays a very important role in the process of learning a language, such as English. To help students improve their vocabulary mastery level, there are various methods that can be used. One of them is using Working with Words through Category Game. In response to this, the program reported in this article was conducted at a junior high school located in the city of Gorontalo Province. The results showed that the use of Working with Words method through Category Game for English vocabulary learning help students increase their English vocabulary mastery level, with the following details: 11 students had 65% to 79% increase of English vocabulary mastery level (Fair); 7 students had 80% to 89% (Distinction); and 5 students had 90% to 100% (High Distinction).